Des quartiers chez les Mayas à l’époque classique ? - Éva Lemonnier (Journal de la Société des Américanistes)
Did neighborhoods exist in Classic Maya societies? In spite of the wealth of archaeological, ethnographical and ethnohistorical data on the topic of neighborhoods (or units defined as such) in the Postclassic, Historic and Modern Maya societies, the existence of this kind of settlement unit, an intermediary category between the household (the extended family) and the settlement (the community), is far from established for the Classic period. This model of social, economic and political organization has been proposed sporadically over the past thirty years. However, few studies have established the archaeological corollaries of such units. Through fieldwork conducted at La Joyanca, we attempt to demonstrate that this small Classic city could have been structured in neighborhoods and to characterize these settlement units. Thus, it presents criteria for the archeological identification and socio-economic interpretation of such Classic units.